1978
DOI: 10.2307/3934
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Stability of Host-Parasite Population Interactions: II. Destabilizing Processes

Abstract: (1) Three categories of biological processes are shown to have a destabilizing inf on the dynamical behaviour of model host-parasite associations: parasit reduction in host reproductive potential, parasite reproduction within a h directly increases parasite population size and time delays in parasite reprod transmission. (2) The importance of parasitic species as regulators of host population growth is examined in light of empirical evidence. Data from two particular laboratory studies used to indicate the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
274
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(283 citation statements)
references
References 19 publications
7
274
0
2
Order By: Relevance
“…Our strategy will be to look for patterns of changes in dynamical behaviour as a contact rate parameter, which measures the infective strength, is increased. Our results will, in the spirit of May and Anderson [l, 16] and Busenberg and van den Driesche [5], identify various thresholds for this contact rate parameter. Moreover, we will find that the pattern of changes of dynamical behaviour for diseases which have a strong influence on fertility is different from that for diseases which have no or only a minor influence on fertility.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Our strategy will be to look for patterns of changes in dynamical behaviour as a contact rate parameter, which measures the infective strength, is increased. Our results will, in the spirit of May and Anderson [l, 16] and Busenberg and van den Driesche [5], identify various thresholds for this contact rate parameter. Moreover, we will find that the pattern of changes of dynamical behaviour for diseases which have a strong influence on fertility is different from that for diseases which have no or only a minor influence on fertility.…”
Section: Introductionsupporting
confidence: 53%
“…This phenomenon does not occur, if the influence on fertility is modelled additively, as was done in [ 16] for the host-parasite model. For model I it can be shown that it is essential that we take the pair formation between infectives and susceptibles into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publications such as Anderson and May (1978) and May and Anderson (1978) heralded the emergence of a sophisticated mathematical modeling approach to understanding the dynamic relationships between parasite and host populations. The subsequent quarter century has witnessed an explosion of research in this area, some strictly theoretical but others blending theory with empiricism, and publications in this field now probably number in the high hundreds.…”
mentioning
confidence: 99%
“…Theoretical studies have shown that parasites have the potential to regulate host abundance through effects on reproduction and survival of the host May and Anderson, 1978). In spite of the increasing recognition of the importance of parasites in population ecology and wildlife conservation, knowledge of host-parasite interactions in the wild remains limited (Smith et al 2009).…”
Section: Introductionmentioning
confidence: 99%